2018
DOI: 10.1186/s13578-018-0211-9
|View full text |Cite
|
Sign up to set email alerts
|

Function of aquaporins in sepsis: a systematic review

Abstract: BackgroundSepsis is a common cause of death in intensive care units worldwide. Due to the high complexity of this immunological syndrome development of novel therapeutic strategies is urgent. Promising drug targets or biomarkers may depict aquaporins (AQPs) as they regulate crucial key mechanisms of sepsis.Main bodyHere we report on base of the current literature that several AQPs are involved in different physiological processes of sepsis. In immune system mainly AQPs 3, 5 and 9 seem to be important, as they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 73 publications
3
53
0
Order By: Relevance
“…AQPs, a family of water channel proteins expressed in various cell types, are implicated in brain edema formation (34). Despite a low protein identity (ϳ11%) with conventional AQPs such as AQP-1 and 4, AQP11 is indeed a functional water channel that permeates both water and glycerol (35)(36)(37).…”
Section: Mir-27a-3p Maintains Bbb Integrity Following Ichmentioning
confidence: 99%
“…AQPs, a family of water channel proteins expressed in various cell types, are implicated in brain edema formation (34). Despite a low protein identity (ϳ11%) with conventional AQPs such as AQP-1 and 4, AQP11 is indeed a functional water channel that permeates both water and glycerol (35)(36)(37).…”
Section: Mir-27a-3p Maintains Bbb Integrity Following Ichmentioning
confidence: 99%
“…Regarding genetic variations, several candidate genes such as those for cytochrome P450 and interleukins have been implicated [ 15 , 16 ]. Aquaporins (AQPs) are related to immune cell and kidney function [ 17 ] and thus, might be of special interest. In the last years, the effects of AQPs on both graft rejection and CMV infection have garnered attention in immunological responses studies [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…AQP3 is an aquaporin that transports water, glycerol and small solutes through the plasma membrane; its function is not limited to liquid transport but also involves cell proliferation, migration, 25) skin hydration, 26) wound healing, 27) and tumorigenesis. 28) There is a high level of AQP3 expression in the intestinal tract, 9) regu-lating the absorption and secretion of liquid and maintaining the steady state. Previous studies have shown that targeted regulation of AQP3 can induce intestinal injury and intestinal bacterial translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that AQPs expressed abundantly in intestinal epithelial cells, and AQPs was involved in the secretion of intestinal mucus. Aquaporin-3 (AQP3) is hydrophobic, weighs 30 kDa and belongs to the aquaporin family, which is expressed in various parts of the intestine, 9) regulating the proliferation and migration of intestinal epithelial cells and transporting glycerol and hydrogen peroxide. In recent years, an increasing number of studies have found that the abnormal expression of AQPs during sepsis induces injuries to multiple important organs, including the heart, brain, kidney, and lung, indicating that AQPs may be an important biomarker of sepsis.…”
Section: Introductionmentioning
confidence: 99%